Memory-enhancing effects of short-term fasting. Issue 1 (1st January 2020) - Totani, Y.; Nakai, J.; Hatakeyama, D.; Ito, E.
Abstract: Many recent reports describe memory-enhancing effects of short-term fasting, but the underlying mechanisms are unknown. In the present study, we demonstrate that the insulin increase occurring during short-term fasting is a key factor in forming the optimal internal state for memory enhancement. The pond snail Lymnaea stagnalis exhibits conditioned taste aversion and recalls it when food-deprived for 1 day (i.e., short-term fasting). Recent experiments showed that this memory recall is regulated by insulin. The results of the present study suggest that cascades from insulin receptor activation to new protein synthesis are involved in the enhancing effects of short-term fasting on memory consolidation and recall.